Accionar terapia respiratoria en paciente femenino de 57 años con fibrosis pulmonar. - Sellan Gavilánez, Anthony Ernesto (2022)
Pulmonary fibrosis is the most common form of interstitial diseases, which is characterized by progressive scarring of the pulmonary structures, which causes loss of lung volume, capacity and elastance. We present a clinical case of a 57-year-old female patient with a history of congestive heart failure plus pulmonary fibrosis, who went to the emergency area due to a clinical picture of two days of evolution characterized by cough, tiredness, headache, sweating, joint pain, tachypnea, tachycardia, to this day beginning to present dyspnea on moderate exertion. The objective of this case study was to identify the actions of respiratory therapy in a female patient with pulmonary fibrosis. As a remarkable conclusion we have those the different respiratory rehabilitation techniques contribute to mitigate the deleterious effects of the pathology and help to improve the quality of life of these patients.